On Lie Ideals and Generalized Jordan Left Derivations of Prime Rings - Rehman, N.; Ansari, A.Z. (Український математичний журнал, 2013)
Let R be a prime ring with characteristic different from 2 and U be a Lie ideal of R. In the paper, we initiate the study of generalized Jordan left derivations on Lie ideals of R and prove that every generalized Jordan left derivation on U is a generalized left derivation on U. Further, it is shown that generalized Jordan left biderivation associated with the left biderivation on U is either U ⊆ Z(R) or a right bicentralizer on U. Нехай R — просте кільцє з характеристикою, відмінною від 2, а U — ідеал Лі цього кільця. У цій статті ми починаємо дослідження узагальнених жорданових лівих похідних на ідеалах Лі кільця R і доводимо, що будь-яка узагальнена жорданова ліва похідна на U є узагальненою лівою похідною на U. Крім того, встановлено, що узагальнена жорданова ліва подвійна похідна, асоційована з лівою подвійною похідною на U, або U ⊆ Z(R), або правим подвійним централайзером на U.